A Study of the Peruvian woman image in magazine advertising - Castillo, Genara (2022)
This research studies the print ads of one and two pages published in Somos magazine (El Comercio). In fact, we examine 520 advertisements with content analysis method; because we would like to determine which kind of women image appear in the Peruvian advertising. For that reason, our aim is to know if women appear in the ads as a person or as a sexual object.